PRODUKSI XILANASE MENGGUNAKAN MEDIA LIMBAH PERTANIAN DAN PERKEBUNAN - Trismilah, Trismilah; Waltam, Deden Rosid (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Waste Agriculture of paddy like hay, bran, chaff and frond of banana and alsowaste plantation of coconut root and cangkang of sawit pregnant [of] lignoselulosa(cellulose, lignine and hemiselulosa).In order to searching alternative materials for the production of xylanase hencedone by research of xylanase production of agriculture waste and plantationwaste like the above. Xylanase produced from Bacillus stearothermopillusDSM 22, using hay, bran, chaff and frond of banana and also coconut root andcangkang of sawit as source of carbon while as source of nitrogen and nutrisi bymolasses and urea. Fermentation done in the erlenmeyer use incubator shakerwith condition of temperature 550C, pH early 8, and agitation 250 rpm. Fromresult of research obtained activity of xylanase highest 0.523 Unit / ml.menit and0.429 Unit / ml.menit at to 30 hours with bran media of oven ( DO) and naturalhay ( JA) respectively with natural bran medium (DA) activity of xylanase highest0.514 Unit / ml.menit at 24 hours fermentation. Fermentation using fermentor withnatural hay and condition of temperature 550C, pH 8, and agitation 250 rpm resultactivity of xylanase highest 2.47 Unit / ml.menit at to 32 hours.